2014
DOI: 10.1128/aem.02790-13
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRs: Molecular Signatures Used for Pathogen Subtyping

Abstract: Rapid and accurate strain identification is paramount in the battle against microbial outbreaks, and several subtyping approaches have been developed. One such method uses clustered regular interspaced short palindromic repeats (CRISPRs), DNA repeat elements that are present in approximately half of all bacteria. Though their signature function is as an adaptive immune system against invading DNA such as bacteriophages and plasmids, CRISPRs also provide an excellent framework for pathogen tracking and evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 92 publications
3
118
1
1
Order By: Relevance
“…CRISPR-based typing methods have been well established for some bacterial species such as M. tuberculosis (Lanotte, 2012) and have been extended to many other human pathogens, as illustrated by their application to recent Salmonella enterica epidemic episodes (Fabre et al, 2012; Shariat et al, 2013). Most often CRISPR-based typing methods provide discriminatory power and epidemiological concordance that are at least equivalent, if not superior, to the commonly used typing methods (Shariat and Dudley, 2014). However, it is essential to assess, on a case-by-case basis, the characteristics of any given CRISPR locus before its use as an epidemiological marker.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR-based typing methods have been well established for some bacterial species such as M. tuberculosis (Lanotte, 2012) and have been extended to many other human pathogens, as illustrated by their application to recent Salmonella enterica epidemic episodes (Fabre et al, 2012; Shariat et al, 2013). Most often CRISPR-based typing methods provide discriminatory power and epidemiological concordance that are at least equivalent, if not superior, to the commonly used typing methods (Shariat and Dudley, 2014). However, it is essential to assess, on a case-by-case basis, the characteristics of any given CRISPR locus before its use as an epidemiological marker.…”
Section: Discussionmentioning
confidence: 99%
“…Active CRISPRs have higher rates of spacer acquisition, which results in more diversity, and so are more useful in differentiating strains. However, less active CRISPR tends to be evolutionarily conserved and so may be useful as markers to detect clonal populations (25,40). Studies showed that the CRISPRs in EHEC tend to be fairly well conserved, so a CRISPR-based PCR assay was developed that enabled the detection of eight major EHEC serotypes with 97.5 to 100% specificity (21).…”
Section: Discussionmentioning
confidence: 99%
“…In general, CRISPR-cas systems have three sections: cas gene cluster, an AT-rich leader sequence, followed by a CRISPR spacer array composed of short (∌24-48 nucleotide) direct repeat sequences separated by similarly sized, unique spacers which are usually derived from mobile genetic elements such as bacteriophages and plasmids [19,20]. Cas genes are found in the majority of CRISPRcontaining genomes and when several CRISPRs of the same CRISPR-cas system are present in a single genome, then usually only a single set of cas genes is clustered with one of the CRISPRs.…”
Section: Introductionmentioning
confidence: 99%